The Influence of Christian Values and Batak Toba Values on the Tourism Service Quality in the Lake Toba Area - Lumbantobing, Paul (Publikasi Indonesia, 2025)
This study aims to analyze the influence of Batak Toba values and Christian values on the tourism service quality. This study is a quantitative study with 267 respondents. Data were analyzed using Smart PLS. The results of this study are that the Batak Toba values and Christian values have a significant influence on the tourism service quality and Batak Toba values has a more significant influence than Christian values on the tourism service quality. While the most significant variable dimension is the hamoraon (wealth) dimension, followed by patience and generosity in second and third positions. This study is input for tourism actors in the Lake Toba Area in improving the tourism service quality, especially by providing guidance on what values need to be prioritized to develop the tourism service quality. This study is still an initial study and has the potential to trigger further, more in-depth research to answer the question of why Batak Toba Values has a more significant influence than Christian values on tourism service quality. Or expand the scope research by examining the influence of Batak Toba values and Christian values on tourist satisfaction and other dependent variables